God’s Forgotten Garden: The Role of Missionary Botany in Sino-European Exchanges - Jooyoung Hong (Religions)
This study explores how European botanical science, introduced by foreign missionaries, transformed the intellectual and environmental landscape of premodern China. By examining the transnational exchange of scientific ideas, the paper highlights the role of missionaries, particularly Jesuits and Protestants, in promoting Western botany within a highly sophisticated Chinese intellectual framework. Despite cultural barriers, missionaries sought to integrate a Christian understanding of nature into Chinese episteme, using botanical studies as a conduit for proselytization. The research focuses on key historical moments, including the Treaty of Nanking, which opened China to Western religious and scientific influences. Findings show that missionaries’ botanical studies, driven by both religious and scientific interests, contributed to cross-cultural intellectual collaboration, leading to ideological–environmental changes. The research reveals that botanical exchange was not limited to science but also intertwined with political, economic, and religious interests. Furthermore, the introduction of experimental science reshaped Chinese approaches to nature, blending European and Chinese intellect systems. Ultimately, this paper argues that foreign missionaries played a crucial role in shaping both modern Chinese botany and global episteme, illustrating how scientific ideas transcended cultural boundaries to create lasting environmental impacts.